Faktor-faktor yang Mempengaruhi untuk Melakukan Medical Tourism : Literatur Review - Dhonna Anggreni; Widya Puspitasari (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO), 2026)
Medical tourism is travel to another region or country for the purpose of obtaining health services while enjoying recreational activities. With advances in information and medical technology, the medical tourism industry has experienced rapid growth, particularly in developing countries. The purpose of this study is to determine the factors that influence someone to undertake medical tourism in a particular country. The research method used is a literature review. The selected journals are journals related to medical tourism. The results show that the factors that influence someone to undertake medical tourism in a particular country are due to lower costs, service quality, geographic location, and the type of care available at health facilities, culture, and language. To be a medical tourism destination for foreign tourists, Indonesia must be able to adapt to market needs. This requires cooperation between sectors to provide high-quality services while maintaining reasonable prices.